2016
DOI: 10.1136/bmjopen-2015-008107
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to care for sick newborns: evidence from the Ghana Newhints cluster-randomised controlled trial

Abstract: ObjectivesTo evaluate the impact of Newhints community-based surveillance volunteer (CBSV) assessments and referrals on access to care for sick newborns and on existing inequities in access.DesignWe evaluated a prospective cohort nested within the Newhints cluster-randomised controlled trial.SettingCommunity-based intervention involving more than 750 000, predominantly rural, population in seven contiguous districts in the Brong-Ahafo Region, Ghana.ParticipantsParticipants were recently delivered women (from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 34 publications
(40 reference statements)
0
35
0
Order By: Relevance
“…Only two of the six infants who died (one death occurred only 10 days after discharge) were taken to a health facility; four stayed at home because their caretaker underestimated the severity of the problem or because the health facility was too far away. These reasons together with cultural practices and/or believing in traditional remedies are well described in the literature [19].…”
Section: Discussionmentioning
confidence: 94%
“…Only two of the six infants who died (one death occurred only 10 days after discharge) were taken to a health facility; four stayed at home because their caretaker underestimated the severity of the problem or because the health facility was too far away. These reasons together with cultural practices and/or believing in traditional remedies are well described in the literature [19].…”
Section: Discussionmentioning
confidence: 94%
“…From these, 58 publications were extracted for further review after examining titles and abstracts. Six studies were identified with relevant data [ 8 – 14 ]. The investigators of these studies were contacted for additional unpublished data, and responses were received from four research groups.…”
Section: Resultsmentioning
confidence: 99%
“… 63 % within seven days of birth, 97 % for two-month follow-up visit No facilitation Female Community Health Volunteers to Facility Based – CHWs Care sought within 28 days of life Morang Innovative Neonatal Intervention (MINI) a [ 11 ] Pakistan 2011 Rural Pakistan Study on identification of etiologies of newborn sepsis Days 2, 6, 13, 20, 27, 34, 41, 48, 59 90 % of enrolled newborns were followed at scheduled visits Provided transport for referral to health facility. Follow-up visit within 24 h for those who did not complete referral Study staff (CHW) to facility, study physicians at facility to tertiary facility No timing indicated Aetiology of Neonatal Infection in South Asia (ANISA) (unpublished) a Africa Ghana 2008 Rural Ghana (2008–2009) RCT on improving neonatal health by training existing community-based surveillance volunteers to identify and conduct ANC/PNC visits Days 1, 3, 7 63 % with at least one postnatal visit, 53 % in representative subsample had first visit on day of delivery or day after Training and incentives for volunteers, materials and supervision for hospital newborn care strengthening and sensitization activities, referral card, counselled on keeping baby warm and frequent bf, dialoged and problem-solved around barriers, 24-h follow-up to check compliance, counselling at 2nd and 3rd PNC visits on five illness signs (stopped or poor feeding, too hot or too cold, difficult or fast breathing, jaundice, less active/lethargy) Community-based surveillance volunteers to hospital or clinic, urban residents tended to comply to hospitals/clinics, rural residents to health center No timing indicated Newhints a [ 8 , 34 ] South Africa 2008 Urban South Africa (2008–2011) RCT on home visit package to improve essential maternal/newborn care and PMTCT First 24–48 h, day 3/4, day 10–14, within 3–4 weeks, after 6 weeks. 59 % received the first post-natal visit and of these 73 % within 48 h after discharge from hospital following delivery Training and incentives referral slips, Partner Defined Quality approach to improve facility quality Pre-existing CHW cadre to local PHC clinic Care sought within 28 days of life Good Start a [ 9 ] Uganda 2009 Rural Uganda (2009–2011) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations